Analysis of Junior High School Students' Mathematical Creative Thinking Abilities on Plane Shapes Subject - Noviyanti, Dina; Selafia, Selafia; Angraini, Lilis Marina (EDUPEDIA Publisher, 2024)
This research aims to determine the mathematical creative thinking abilities of class VII students at SMPN 6 Siak Hulu. In this study, four indicators were used, namely fluency indicators, originality indicators, flexibility indicators, and elaboration indicators. In the learning carried out, especially in mathematics learning, students must have the ability to think creatively and mathematically. The ability to think creatively mathematically is the ability to think to find new ideas or thoughts in general or original with the aim of providing definite and precise results. The subjects in this research were 28 class VII students using qualitative descriptive methods. The instrument in this research used four essay questions and interviews on mathematical creative thinking abilities. The results of research on students' mathematical creative thinking abilities at SMPN 6 Siak Hulu obtained meager results. The average percentage for all indicators is 18%. This research aims to determine the mathematical creative thinking abilities of class VII students at SMPN 6 Siak Hulu. In this study, four indicators were used, namely fluency indicators, originality indicators, flexibility indicators, and elaboration indicators. In the learning carried out, especially in mathematics learning, students must have the ability to think creatively and mathematically. The ability to think creatively mathematically is the ability to think to find new ideas or thoughts in general or original with the aim of providing definite and precise results. The subjects in this research were 28 class VII students using qualitative descriptive methods. The instrument in this research used four essay questions and interviews on mathematical creative thinking abilities. The results of research on students' mathematical creative thinking abilities at SMPN 6 Siak Hulu obtained meager results. The average percentage for all indicators is 18%.